DIRECTIONS OF IMPROVEMENT OF FINANCIAL AND ECONOMIC ACTIVITY OF THE ENTERPRISE AT THE PRESENT STAGE - Zhakupova Bakitgul; Aldashova Gulziya; Aliyeva Ardak; Zhienbayev Ulan (Academic Journal of Physical and Chemical Sciences, 2020)
An essential role in the management of financial and economic life of the enterprise is assigned to financial management, which is understood as the movement of managing financial resources and funds of funds to achieve the goals of the enterprise and solve tactical problems. Based on the results of the analysis of the financial condition of ADN LLP it can be seen that in the period under review, the structure of assets and liabilities of the enterprise are changing for the worse. Considering the liabilities of the balance sheet of ADN LLP, it should be noted that the property of the enterprise is substantially formed by borrowed funds, namely long-term and short-term liabilities. The analysis of the liquidity of the balance sheet of the company showed that the organization does not have enough cash to cover its long-term liabilities.